Two Objects of the KGB Secret Activities - Anušauskas, Arvydas (Genocidas ir rezistencija, 1998)
In this article, we will expose two aspects of the KGB’s activities that are, from a surface point of view, not very closely interrelated – technological espionage and the fight against supporters of Lithuanian independence. All of these were carried out by the same organiser of covert activities – the KGB. The diversity of its methods and operations, the convergence of its covert operations, mixed and uniform methods make it necessary to investigate and gain a better understanding of the KGB’s entire arsenal.
Keywords: KGB; KGB methods; antisoviet resistance; economy; science